A Novel Methodology for Resource Allocation in D2D Communication Based on Hypergraph - Arun Kumar Sharma (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The exploration of Device-to-Device (D2D) communication has become well-known as a prominent alternative to alleviate congestion in licensed spectrum bands. D2D communication serves as a cornerstone in offloading cellular traffic and ameliorating network congestion, thereby reducing latency and enhancing network responsiveness. The present work describes a research study that uses a Hypergraph-based technique to allocate resources in D2D communication within a Hexagonal Cellular network. The research addresses resource allocation difficulties using Linear Programming by formulating constraint matrices and right-hand side vectors. The simulation examines the allocation of resource blocks to cellular users and how it affects data rates, revealing important insights for system optimization. The complexity study of the Hypergraph-based technique for Resource Allocation suggests that its scalability is directly proportional to the cube of the sum of A and B, where A represents the number of cellular users and B represents the number of D2D couples. Graphical analyses demonstrate significant patterns: the correlation between resource blocks and cellular users highlights the necessity for effective allocation schemes, while the influence of resource availability on data rates stresses the significance of optimal allocation systems. Finally, the relationship between throughput and the distance between D2D users emphasizes the impact of geographical factors on performance. Potential areas for future research involve simplifying resource allocation methods and increasing cell capacity to improve D2D communication and the performance of cellular networks, specifically in optimizing channel capacity and spectral efficiency.